Modulation of value-based decision making behavior by subregions of the rat prefrontal cortex. - Verharen, Jeroen P. H.; den Ouden, Hanneke E. M.; Adan, Roger A. H.; Vanderschuren, Louk J. M. J. (Psychopharmacology, 2020)
Rationale: During value-based decision-making, organisms make choices on the basis of reward expectations, which have been formed during prior action-outcome learning. Although it is known that neuronal manipulations of different subregions of the rat prefrontal cortex (PFC) have qualitatively different effects on behavioral tasks involving value-based decision-making, it is unclear how these regions contribute to the underlying component processes. Objectives: Assessing how different regions of the rodent PFC contribute to component processes of value-based decision-making behavior, including reward (or positive feedback) learning, punishment (or negative feedback) learning, response persistence, and exploration versus exploitation. Methods: We performed behavioral modeling of data of rats in a probabilistic reversal learning task after pharmacological inactivation of five PFC subregions, to assess how inactivation of these different regions affected the structure of responding of animals in the task. Results: Our results show reductions in reward and punishment learning after PFC subregion inactivation. The prelimbic, infralimbic, lateral orbital, and medial orbital PFC particularly contributed to punishment learning, and the prelimbic and lateral orbital PFC to reward learning. In addition, response persistence depended on the infralimbic and medial orbital PFC. As a result, pharmacological inactivation of the infralimbic and lateral orbitofrontal cortex reduced the number of reversals achieved, whereas inactivation of the prelimbic and medial orbitofrontal cortex decreased the number of rewards obtained. Finally, using simulated data, we explain discrepancies with a previous study and demonstrate complex, interacting relationships between conventional measures of probabilistic reversal learning performance, such as win-stay/lose-switch behavior, and component processes of value-based decision-making. Conclusions: Together, our data suggest that distinct components of value-based learning and decision-making are generated in medial and orbital PFC regions, displaying functional specialization and overlap, with a prominent role of large parts of the PFC in negative feedback processing.